Transoral endoscopic examination of head and neck region. Issue 4 (26th April 2018) - Hamada, Kenta; Ishihara, Ryu; Yamasaki, Yasushi; Akasaka, Tomofumi; Arao, Masamichi; Iwatsubo, Taro; Shichijo, Satoki; Matsuura, Noriko; Nakahira, Hiroko; Kanesaka, Takashi; Yamamoto, Sachiko; Takeuchi, Yoji; et al.
Abstract : Transoral endoscopy with narrow band imaging (NBI) is useful for early detection of head and neck (HN) cancer. However, the lateral and anterior walls of the oropharynx, postcricoid area, and posterior wall of the hypopharynx are difficult to observe using transoral endoscopy. Advanced cancers in these regions may be missed even when NBI is used. This report highlights a method of transoral endoscopic examination of the HN region. For observation of the oral cavity and oropharynx, it is important to observe these regions without using a mouthpiece. Wide opening of the mouth facilitates observation of the oral cavity and oropharynx. Moreover, visibility of the oropharynx, including the anterior wall, is dramatically improved, when the patient positions the tongue forward and says 'aaah.' This technique also facilitates observation of the dorsum of the tongue, which is difficult to observe from a tangential view when using a mouthpiece. To observe the hypopharynx, the Valsalva maneuver is very useful. Patient cooperation is important when observing the HN region thoroughly to gain clear endoscopic views. Narcotic drugs, such as pethidine hydrochloride, are ideal for conscious sedation and reduce the gag reflex while still allowing patient cooperation. From the oral cavity to the hypopharynx, including the lateral and anterior walls of the oropharynx, postcricoid area, and posterior wall of the hypopharynx, most of the HN region can be observed during routine examination using transoral endoscopy without any special devices.